The importance of critical thinking in the education of junior school age students - Isaxanova Moxidil Erkinovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, an example of the importance, method and use of pedagogical technology in developing free, independent, critical thinking in the educational process is presented.